2014
DOI: 10.4314/gjpas.v20i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profitability analysis of selected rainfed and irrigated food crops in Adamawa state, Nigeria

Abstract: The study aimed at conducting a comparative profitability analysis of selected rainfed and irrigated food crops in Adamawa state, Nigeria. Two hundred and ten (210) (with 105 each from rainfed and irrigated) farmers growing rice, maize, tomato and pepper were randomly sampled for the 2007, 2008 and 2009 seasons respectively. The analytical tools used to achieve the objectives of study include descriptive statistics, profit function and farm budgeting techniques. Results revealed that 54.29 % of the farmers und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…As one of the factor inputs in groundnut production, seed was positive and significant with an elasticity coefficient of 0.430implying that a 5% increase in the quantity of seed would increase output by 43%. This result agrees with the findings of [20] who found that increase in seed input can increase agricultural productivity. The elasticity coefficient of farming experience was positive (0.049) and statistically significant at 1% probability level possibly depicting the impact of experience on groundnut production.…”
Section: Regression Analysis Resultssupporting
confidence: 93%
“…As one of the factor inputs in groundnut production, seed was positive and significant with an elasticity coefficient of 0.430implying that a 5% increase in the quantity of seed would increase output by 43%. This result agrees with the findings of [20] who found that increase in seed input can increase agricultural productivity. The elasticity coefficient of farming experience was positive (0.049) and statistically significant at 1% probability level possibly depicting the impact of experience on groundnut production.…”
Section: Regression Analysis Resultssupporting
confidence: 93%
“…Also, the coefficient of household size is statistically significant at 1% level and it had a negative sign which implies that the inefficiency among maize farmers in the study area reduces with an increase in number of adult in the household who participated in farming activities. This is in consonance with the findings of Tashikalma et al (2014) who reported that greater family size of average working age increases efficiency because most farmers are financially constrained.…”
Section: Maximum Likelihood Estimate Of the Stochastic Frontier Cost supporting
confidence: 91%
“…Several studies revealed that, there is much need to increase food output in order to: feed the increasing population; earn the needed foreign exchange to import non-food needs; to generate savings for investment; and to preserve and conserve the natural resource base to enhance its productivity [7,8]. Consequently, the approach to increasing agricultural production in a country through irrigation farming is a major panacea, if the problem of food shortage in the country is to be addressed [9].…”
Section: Introductionmentioning
confidence: 99%